Pengaruh Brand Image Dan Brand Trust Terhadap Minat Beli Pada E-Commerce Bukalapak Di Surabaya - Salsabil Azizah; Nuruni Ika Kusuma Wardhani (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The growth of digitalization that occurs at this time, makes internet users increasing. The development of the internet or online media, provides convenience in finding information and has become a business area, or now commonly referred to as online business (e-commerce) which has many advantages, so that buying interest is very important for the people of Indonesia. This research aims to determine brand image and brand trust to influence Bukalapak's e-commerce buying interest. The population in this study were visitors who had shopped at Bukalapak Indonesia e-commerce in the Surabaya area. This study applies the non probability sampling method in taking samples and uses accidental sampling techniques. There were 65 respondents and were analyzed using Partial Least Square (PLS). Based on the results of the study, it shows that brand image and brand trust have a significant positive influence on the buying interest of Bukalapak e-commerce visitors in Surabaya. Keywords: Brand Ambassador; Electronic Word Of Mouth; Purchase Intention